SUSTAINABLE AGRICULTURE DEVELOPMENT: A PRACTICE IN MALANG REGENCY, INDONESIA - Arni Noventi, Ike (FIA UB, 2015)
Sustainable Agriculture Development: Practice in Malang Regency, Indonesia. The practice of green revolution has proven cause natural and social degradation. Therefore, the local government shifted the agricultural practice to sustainable agriculture system. This academic research is aimed to explain the practice of sustainable agriculture development in Malang Regency and discover why the natural and social degradation still exist by addressing (1) How many programs conducted by local government in developing agriculture sector? (2) Do those programs support the practice of sustainable agriculture? and (3) What are the supporting and inhibiting factors in developing sustainable agriculture?. This research uses qualitative approach combines with descriptive research method. The result shows that Local Government of Malang Regency has conducted fifty one agriculture programs, however only 45,10% of those programs support the practice of sustainable agriculture development. There are at least two supporting factors in developing sustainable agriculture in this regency; namely clear legal framework and sufficient infrastructure. However, there are at least five inhibiting factors which one of them is socio-cultural condition of the society.